2013
DOI: 10.1038/bjc.2012.593
|View full text |Cite
|
Sign up to set email alerts
|

Epidural methadone results in dose-dependent analgesia in cancer pain, further enhanced by epidural dexamethasone

Abstract: Background:This study was designed to evaluate the role of epidural methadone-lidocaine in cancer pain combined or not to epidural dexamethasone.Methods:In all, 72 cancer patients, 32- to 67-year-old were randomized to six groups (n=12) and prospectively studied to examine analgesia and adverse effects for 3 weeks. Patients received single-dose protocol epidural test drugs: Control group (CG) received epidural 40-mg lidocaine diluted to 10-ml volume with saline. Dexamethasone group (DG) 40-mg lidocaine plus 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
21
0
3
Order By: Relevance
“…277 This approach is a valuable tool to improve analgesia for patients who have pain from a variety of anatomic locations (eg, head and neck, upper and lower extremities, trunk). [278][279][280][281] However, due to the risk of catheter migration and infection risk, consider limiting the duration of use to several days.…”
Section: Interventional Strategiesmentioning
confidence: 99%
“…277 This approach is a valuable tool to improve analgesia for patients who have pain from a variety of anatomic locations (eg, head and neck, upper and lower extremities, trunk). [278][279][280][281] However, due to the risk of catheter migration and infection risk, consider limiting the duration of use to several days.…”
Section: Interventional Strategiesmentioning
confidence: 99%
“…When no difference between nociceptive and neuropathic pain was made, no difference in pain relief between morphine and methadone could be observed. A more recent systematic review, based on 4 RCTs published after the 2007 Cochrane review, showed no difference in effectiveness between methadone compared to other strong opioids in 2 RCTs . Two other RCTs used in this systematic review evaluated the effect of opioid rotation to methadone: in one study no conclusion on the efficacy of methadone in treatment of cancer pain could be presented due to the number of dropouts, and the other reported a decrease in pain intensity switching from morphine to methadone and a patient preference for methadone .…”
Section: Discussionmentioning
confidence: 82%
“…Dexamethasone has been added to local anesthetics, amongst numerous adjuvants, such as clonidine, buprenorphine, neostigmine, tramadol, epinephrine, which have helped, improve postoperative analgesia (Bailard et al, 2014). Clinical studies in regional anesthesia, have time and again, assessed the ef icacy of dexam-ethasone mixed with local anesthetics and instilled perineurally, including epidural (Lauretti et al, 2013;Naghipour et al, 2013) brachial plexus (Persec et al, 2014) , femoral and sciatic (Fredrickson et al, 2013) and facial and dental blocks (Jürgens et al, 2012).…”
Section: Methodsmentioning
confidence: 99%